2014
DOI: 10.1108/ssmt-10-2013-0028
|View full text |Cite
|
Sign up to set email alerts
|

Voids investigation in solder joints performed with vapour phase soldering (VPS)

Abstract: Purpose – The main advantages of vapour phase soldering are a non-oxygen environment, the elimination of overheating and the possibility of the vacuum application, which can guarantee undeniably higher quality of solder joints, especially as regards void formation. These features are less affected by the alloy composition. The paper aims to discuss these issues. Design/methodology/approach – The quality of solder joints made in two VPS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 4 publications
1
34
0
1
Order By: Relevance
“…Medgyes et al investigated the electrochemical migration on biodegradable materials [15], and showed that due to better wetting on different biodegradable substrates, the failure criteria may occur earlier during migration tests, compared to conventional PCBs. Our previous work focused on Cellulose Acetate (CA) and PLA materials [16][17][18]; the investigations were combined with vapour phase soldering (VPS) joining method, where quality concerning results were similar to the typical findings of VPS investigations [19][20][21][22][23] with lead-free solder alloys. Our papers also showed limiting factors of solder joint production (the biodegradable substrates have lower melting point and lower glass transition temperature than standard FR4 PCBs), and limiting mechanical parameters of the produced PCBs.…”
Section: Introductionmentioning
confidence: 82%
“…Medgyes et al investigated the electrochemical migration on biodegradable materials [15], and showed that due to better wetting on different biodegradable substrates, the failure criteria may occur earlier during migration tests, compared to conventional PCBs. Our previous work focused on Cellulose Acetate (CA) and PLA materials [16][17][18]; the investigations were combined with vapour phase soldering (VPS) joining method, where quality concerning results were similar to the typical findings of VPS investigations [19][20][21][22][23] with lead-free solder alloys. Our papers also showed limiting factors of solder joint production (the biodegradable substrates have lower melting point and lower glass transition temperature than standard FR4 PCBs), and limiting mechanical parameters of the produced PCBs.…”
Section: Introductionmentioning
confidence: 82%
“…voiding, paste sputtering, tombstone failures, etc…) [5]. The heat transfer coefficient during the VPS process can be ~3 times higher than the heat transfer coefficient in a forced convection reflow oven [6].…”
Section: Introductionmentioning
confidence: 99%
“…After investigating different case studies in the field of VPS [7][8][9][10][11][12], it was supposed, that different material properties may reveal differences in the heat transfer process during VPS with the same oven settings, resulting in different solder joint quality for each setup. The discussion of this difference is clearly missing from current literature.…”
Section: Introductionmentioning
confidence: 99%